Infrastructure and Labour Productivity Convergence in Gunungkidul Region - Udjianto, Didit Welly; Susanto, Joko; Purwiyanta, Purwiyanta (Universitas Negeri Semarang, 2018)
The paper examines whether labour productivity converges or diverges. This research estimates the convergence of labour productivity, and the effects of infrastructure to support this convergence, based on a set panel data comprising 18 districts in Gunungkidul Regency from 2009 to 2016. The secondary data published by the Statistics of DIY is used in this study. The infrastructure includes educational facilities, health facilities and length of the road. A fixed-effect model presents that there is a process of convergence of labour productivity among districts in Gunungkidul Regency. Moreover, the result shows that infrastructure has a positive effect on labour productivity. This research finds that labour productivity, in the lagging districts, tends to grow faster than advanced ones. Thus, the labour productivity gap between districts will disappear. A better educational and health facilities supports the speed of the knowledge transfer process to generate productive labour. For supporting the convergence of labour productivity, the local government has to improve infrastructure especially in lagging districts. Likewise, improvements in road facilities solve the problem of high-cost distribution to increase labour productivity.